TIOCONAZOLE LOADED MUCOADHESIVE MICROSPHERES FOR THE TREATMENT OF VAGINAL CANDIDIASIS - SABRY, SHEREEN AHMED (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: The principal objective of this research work was to formulate tioconazole into mucoadhesive microspheres which were inserted into the vagina for sustaining the anti-fungal activity and protecting the liver and the kidney from the harmful drug side effects. Methods: Microspheres were prepared by the emulsion solvent evaporation method, using different ratios of the drug with either ethyl cellulose N14 or hydroxypropylmethylcellulose K100M (HPMC K100M) as mucoadhesive polymers. The formulated microspheres were evaluated for the particle size, entrapment efficiency, yield percentage, mucoadhesion strength, swelling percentage, pH, in vitro release of the drug and finally in vitro antifungal activity. Results: The optimized formulae were F3 and F6, which showed drug entrapment of 88.4±2.5 % and 97.8±1.6 %, yield percentage of 85.0±2.3% and 95.2±1.2%, mucoadhesion strength of 31.5±1.6 and 38.1±1.6 *103 dyne/cm2, swelling percentages of 143.1±1.3 and 154.2±0.8, pH of 4.7±0.1 and 4.6±0.5, and particle size of 400±3.5 µm and435±7. 8 µm respectively. F3 and F6 released about 72.8%±3.2 and 58.4%±2.7 of the drug after 8 h respectively. F3 and F6 showed a significant anti-fungal activity. Conclusion: Ethyl cellulose and hydroxyl propyl methylcellulose mucoadhesive microspheres are considered a good way to increase the duration of the anti-fungal activity of tioconazole with minimum side effects.